Physical Chemistry of Semiconductor Materials and Interfaces XX (SPIE / International Society for Optical Engineering, 2021)
Proceedings of SPIE offer access to the latest innovations in research and technology and are among the most cited references in patent literature. The papers in this volume were part of the technical conference on Physical Chemistry of Semiconductor Materials and Interfaces XX held on 1-5 August 2021, San Diego, California, United States.